Improving The Mechanical Properties Of Gray Cast Iron By Controlling The Solidification Rate (Czech Journal of Multidisciplinary Innovations, 2025)
This article aims to improve the mechanical properties of the ingot by controlling the cooling process of the ingot by sending air at a certain pressure in addition to the cooling rate during the cooling of gray cast iron melted in an induction furnace in a sand-clay mold